ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN UMKM DALAM MEMILIH LEMBAGA KEUANGAN MIKRO SEBAGAI SUMBER PEMBIAYAAN - Handayani, Susi (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2015)
This study aims to examine the behavior of consumers, the factors influencing the selection of microfinance institutions sources of funding for SMEs. The study was conducted because of the difficulty SMEs to access financial institutions, especially the Bank, because a lot of procedures to go through as requirements. What factors are underlying the selection of financial institutions for SME capital sources. This study will determine what factors are the basis for SMEs in choosing a source of financing for their business. The result is expected to be useful for the government and relevant agencies in reviewing procedures and filing system of credit for SMEs. It is very necessary especially for SMEs is the foundation of Indonesias economy and should be supported to be more sturdy. SME growth will help the government, one of them in terms of employment.Research is associative, because it intends to examine the relationship between the independent variables on the dependent variable. The results showed that simultaneous personal factors, psychological, social and cultural significant effect on the selection of financial institutions. However partially show different things. Partially personal factors influence the consumers decision, but the factor of psychological, social and cultural decision does not affect the consumer in choosing a financial institution.